ANALISIS HUKUM TANGGUNG JAWAB KARYAWAN ATAS PELANGGARAN NON DISCLOSURE AGREEMENT PADA AGENSI KREATIF - NIM. A1011211033, TEGUH BAKANANTA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The rapid development of the creative industry, has brought new challenges related to the protection of trade secrets, especially in the form of digital assets. Creative agencies, as providers of branding and social media management services, inherently manage strategic information and client digital assets that have high economic value and are confidential. The existence of a Non-Disclosure Agreement (NDA) is a vital legal instrument to bind employees in maintaining the confidentiality of such information. However, the ease of disseminating digital assets through online platforms, such as sharing Google Drive links, creates vulnerabilities to employee negligence, which can lead to trade secret violations and losses for both clients and the agency itself. This research analyzes the legal responsibility of employees for NDA violations in creative agencies, focusing on a case of digital asset misuse (product cutout photos) due to employee negligence. The research method used is normative juridical with a case study approach, examining laws and regulations related to the case. Data was collected through interviews with relevant parties and analysis of the NDA document used by the agency. This study aims to identify relevant forms of legal protection and analyze the effectiveness of NDAs and efforts to handle trade secret violation cases. The research findings indicate that even though the agency has an NDA, employee negligence can still lead to digital asset trade secret violations. The case at Clico Creative Agency, which was resolved through mediation, highlights the complexity of handling trade secret violation cases involving internal negligence. Therefore, a comprehensive protection strategy is needed, not only relying on legal instruments such as NDAs. The implementation of these steps is expected to minimize the risk of violations, maintain client trust, and ensure the sustainability of creative agency businesses in the evolving digital era. Keywords: Trade Secret, Non-Disclosure Agreement (NDA), Creative Agency, Digital Assets, Employee Responsibility. Abstrak Pesatnya perkembangan industri kreatif, telah memunculkan tantangan baru terkait perlindungan rahasia dagang. Agensi kreatif, sebagai penyedia layanan branding dan manajemen media sosial, secara umum mengelola informasi strategis dan aset digital klien yang memiliki nilai ekonomi tinggi dan bersifat rahasia. Keberadaan Non-Disclosure Agreement menjadi instrumen hukum vital untuk mengikat karyawan dalam menjaga kerahasiaan informasi tersebut. Namun, kemudahan penyebaran aset digital melalui platform daring, seperti berbagi link Google Drive, menimbulkan kerentanan terhadap kelalaian karyawan, yang dapat berujung pada pelanggaran rahasia dagang dan kerugian bagi klien serta agensi itu sendiri. Penelitian ini menganalisis tanggung jawab hukum karyawan atas pelanggaran NDA pada agensi kreatif, dengan fokus pada kasus penyalahgunaan aset digital (foto cutout produk) yang digunakan oleh brand lain tanpa izin, yang diakibatkan oleh kelalaian karyawan. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan studi kasus, mengkaji peraturan perundang-undangan yang berkaitan. Data dikumpulkan melalui wawancara dengan pihak terkait dan analisis dokumen NDA yang digunakan. Hasil penelitian menunjukkan bahwa meskipun agensi telah memiliki NDA, kelalaian karyawan tetap dapat menyebabkan pelanggaran rahasia dagang. Kasus yang terjadi di Clico Creative Agency, yang diselesaikan melalui mediasi kepada karyawan, menyoroti kompleksitas penanganan kasus pelanggaran rahasia dagang. Oleh karena itu, diperlukan strategi perlindungan yang komprehensif, yang tidak hanya mengandalkan instrumen hukum seperti NDA, Implementasi langkah-langkah ini diharapkan dapat meminimalkan risiko pelanggaran, menjaga kepercayaan klien, dan memastikan keberlanjutan bisnis agensi kreatif di era digital. Kata Kunci: Rahasia Dagang, Non-Disclosure Agreement (NDA), Agensi Kreatif, Aset Digital, Tanggung Jawab Karyawan.